Social inequalities in the use of contraceptives in adult women from Southern Brazil - Tonantzin Ribeiro Gonçalves; Heloísa Marquardt Leite; Fernanda Souza de Bairros; Maria Teresa Anselmo Olinto; Nêmora Tregnago Barcellos; Juvenal Soares Dias da Costa (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To describe the contraceptive methods used by adult women and the associated socioeconomic and demographic factors. METHODS: Population-based cross-sectional study with 20 to 49-year-old women from São Leopoldo, state of Rio Grande do Sul, in 2015. Three outcomes were considered to analyze the association with demographic and socioeconomic characteristics: use of oral contraceptive pills, tubal ligation and male condom. The crude prevalence ratios, stratified by age, and 95% confidence intervals (95%CI) were obtained using Poisson regression, taking the experimental error into account. RESULTS: A total of 736 women, aged from 20 to 49 years old, were evaluated. The prevalence of the use of oral contraceptive pills, tubal ligation and male condom were respectively 31.8% (95%CI 28.4-35.3), 11.1% (95%CI 9.0-13.6) and 10.9% (95%CI 8.7-13.3). In addition, 10.5% (n = 77) of the women reported making combined use of oral contraceptive pills and condom. In the stratified analysis, younger women with lower education level and from lower social classes reported less use of oral contraceptive pills. Tubal ligation was more prevalent among the lower social classes, but only in the age group from 30 to 39 years old. No differences were found in relation to male condom. CONCLUSIONS: The results indicated that differences persist in relation to contraception, which can be associated with both the difficulties of access to these inputs and the frailty of actions in reproductive health to achieve the needs and preferences of women who are more socially vulnerable.